ETNOBOTANI TANAMAN OBAT MASYARAKAT SUKU DAYAK BAKUMPAI DI DESA LEMO II KECAMATAN TEWEH TENGAH KABUPATEN BARITO UTARA - Maulid Hidayat; Rosidah Radam; Henny Arryati (Jurnal Sylva Scienteae, 2020)
This study aims to identify the types of traditional medicinal plants and plant parts that can be used by the Dayak Bakumpai tribe community in Lemo II village including analyzing how to treat these traditional medicinal plants to cure a disease and analyze how many dayak Bakumpai tribes still use plants traditional medicine in lemo II village, central teweh sub-distric, North Barito Regency. the data was obtained by interviewing the village physician using snowbal sampling technique. The results of this study of medicinal plants used consisted of 20 types of Pungkala Tawar (Costus speciusus), Bemban (Donax caniformis), Sasingut Pusa (Orthosiphan oristatus), Kangkawang (Shorea macrophylla), Penawar Sampai (Baccaurea lanceolata), Kalampeso (Helminthostacyys zeylanica), Teken Parei (Helminthostacyys zeylanica), Lukud (Asplenium nidus L.), Ligundi (Vitex trifolia L.), Cermin Pilanduk (Omalanthus grandifolius Ridl), Karamunting (Melastoma malabatrhricum L), Kayu Matan Andau (Lepisanthes amoena), Uhat Bahenda (Coscinium fenestratum), Mintu (Ligudium circinatum), Cocor Bebek (Kalanchoe pinnata), Sungkai (Peronema canescens), Kapas Rampit (Gossypium acuminatum Roxb.), Lambiding (Stenochloena palustris), Kenanga Hutan (Cananga odorata), and Krukutayu (Ageratum conyzoides L.). How to cultivate these plants with a variety of ways such as mashed, boiled, baked, soaked, dried and etc.Keywords: Ethnobotany; Medicinal Plants; Dayak Bakumpai